Hydrogen sulfide as a novel mediator for pancreatic pain in rodents. Issue 6 (6th February 2009) - Nishimura, S; Fukushima, O; Ishikura, H; Takahashi, T; Matsunami, M; Tsujiuchi, T; Sekiguchi, F; Naruse, M; Kamanaka, Y; Kawabata, A
Abstract : Objective: Hydrogen sulfide (H2 S) is formed from l -cysteine by multiple enzymes including cystathionine-γ-lyase (CSE) in mammals, and plays various roles in health and disease. Recently, a pronociceptive role for H2 S in the processing of somatic pain was identified. Here, the involvement of H2 S in pancreatic pain is examined. Methods: Anaesthetised rats or mice received an injection of NaHS, a donor for H2 S, or capsaicin into the pancreatic duct, and the expression of spinal Fos protein was detected by immunohistochemistry. Pancreatitis was created by 6 hourly doses of caerulein in unanaesthetised mice, and pancreatitis-related allodynia/hyperalgesia was evaluated using von Frey hairs. CSE activity and protein levels in pancreatic tissues were measured using the colorimetric method and western blotting, respectively. Results: Either NaHS or capsaicin induced the expression of Fos protein in the superficial layers of the T8 and T9 spinal dorsal horn of rats or mice. The induction of Fos by NaHS but not capsaicin was abolished by mibefradil, a T-type Ca 2+ channel blocker. In conscious mice, repeated doses of caerulein produced pancreatitis accompanied by abdominal allodynia/hyperalgesia. Pretreatment with an inhibitor of CSE prevented the allodynia/hyperalgesia, but not the pancreatitis. A single dose of mibefradil reversed the established pancreatitis-related allodynia/hyperalgesia. Either the activity or protein expression of pancreatic CSE increased after the development of caerulein-induced pancreatitis in mice. Conclusions: The data suggest that pancreatic NaHS/H2 S most probably targets T-type Ca 2+ channels, leading to nociception, and that endogenous H2 S produced by CSE and possibly T-type Ca 2+ channels are involved in pancreatitis-related pain.